Shear Strength Characteristics of Coir Fibre Stabilised Stone Matrix Asphalt Mixtures - S, Bindu; S, Beena (International Journal of Sustainable Construction Engineering and Technology, 2015)
The triaxial test measures the mix stability in the form of shear strength and gave better information for the prediction of field performance. The stresses acting on the laboratory specimen during the test simulate the state of stresses existing in the pavement. The Stone Matrix Asphalt mixtures (SMA)were investigated using triaxial shear strength testing at 50.8 mm/min ram rate loading at 60°C to investigate the effect of additive, coir fibre on the strength properties by varying the percentages of fibre. SMA without fibre is taken as the control mixture. The test was conducted at 0, 50, 75 and 100kPa confinements. The Mohr-Coulomb failure theory was used to analyze the test data and the analysis shows that the SMA stabilized mixtures had highest cohesion and shear strength as compared to the control mixture, but almost similar angle of internal friction value. The higher values of cohesion and shear strength can be associated to a fibre content of 0.3% and the percentage increase in cohesion is about 53% with respect to the control mixture. This shows that the mixture has greater resistance to shearing stresses than the control mixture. There is a trend that the strain at failure increases with increasing confinement pressure, indicating their stress dependent behaviour. The stress-strain curves indicate that the peak stress developed and the time of its occurrence is higher in stabilized mixtures when compared to those of the control mixture. For stabilized mixtures, it is observed that the shape change of the stress-strain curves is more gradual with increase in fibre content and brittle type failure does not seem to occur as in the case of control mixture.